THE POWER OF TWO STRATEGY EFFECTIVENESS ON TEACHING READING - Surti Milarisa; Onika Riski Handayani (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
This research analyzed the effect of teaching reading through the power of two strategy in teaching reading. The objective of the research was to investigate whether is there the significant effect of using the power of two strategy in teaching reading at the tenth-grade students of SMA Muhammadiyah Tanjung Redeb. In this research, the researcher applied quantitative research. Population of this research were all of the students at the tenth grade which consist of 103 students. The sample of this research was one class of the tenth grade. The number of students which took as a sample was 30 students. The researcher applied the test to collected the data, then the researcher did t-test to knew the effect of teaching reading through the power of two strategy.The data collected in this research analyzed by using t-test and mean of pre-test and post-test. According to the result of statistically calculation, t obtaint = (-7,085) and the value of “t” on the t table = t0.05 = (-1,69913), It meant -7,085 < -1,69913. For the mean of the test there was an increase as much 12,33. Then the p value also smaller than the standart of level significant (0,000 < 0,05). Based on the result of statistically calculation of this research, it can be concluded that the power of two strategy has significant effect in teaching reading at the tenth-grade students of SMA Muhammadiyah.